Entrenamiento de suspensión y su influencia en la postura corporal de jóvenes - Guaipacha Chinchi, Joselyn Patricia (2023)
Based on body situations, we have observed the need for more knowledge and adequate information on young athletes as non-athletes on body status. The research was carried out with young swimmers from the city of Riobamba, Spain. "Extreme Athletic Club" with the theme titled "Suspension training and its influence on body posture in young people". It aimed to analyze suspension training in an age range of 11 to 15 years, applying a quasi-experimental, cross-sectional field research with a probabilistic sampling. For the present investigation, a test was applied as a research technique. As a research instrument with the application of a test called "Posturogram," and with the support of the Kinovea software with which the body postures are verified, all this focused on young people. After this, a suspension training program was applied for 12 weeks, working three days a week, obtaining as results rejected the null hypothesis and the alternative hypothesis is accepted. In conclusion, suspension training helped to correct body posture, sometimes determining an optimal body state and a slight deviation in young swimmers.